WEWENANG BAWASLU DALAM PENYELESAIAN SENGKETA PROSES PEMILU DI KOTA PALANGKA RAYA - Endrawati Endrawati (Fakultas Hukum Universitas PGRI Palangkaraya, 2019)
Elections are a means of popular sovereignty to elect DPR members, DPD members, the President and vice-president, and to elect DPRD members which are carried out directly, publicly, freely, confidentially, honestly and fairly in the Unitary State of the Republic of Indonesia based on the Pancasila and the State Constitution Republic of Indonesia in 1945. Based on Law No. 7 of 2017, the first time the General Election was held simultaneously included the election of members of the DPR, DPD members, president and vice president, and to elect DPRD members this had an impact on the complexity of holding it. Elections are carried out through several stages and each stage determines whether or not an Election participant passes to proceed to the next stage. The breakout is determined by the organizer of the election in this case the General Election Commission (KPU) through a decision letter or Minutes. As an election supervisory body, Bawaslu has the authority to settle disputes that arise as a result of KPU Decisions or Minutes. Dispute Resolution is carried out through mediation and adjudication within a maximum of 12 working days from the diregister Dispute Request.